Customer Satisfaction with Massage Service (Sport Personnel and General) - Iskandar; Y. Tovan Juni Samudro; Uray Gustian (Universitas Majalengka, 2021)
The problem in this study is how the level of customer service satisfaction for massage for sports / general practitioners. This study aims to see the level of customer satisfaction with massage services (sports and general practitioners) with variables 1. Reliability (reliability), 2. Responsiveness (responsiveness), 3. Assurance (assurance), 4. Empathy (empathy), 5. direct evidence (tangibles). Ex post facto quantitative descriptive research design for customers who had received massage services from October 2020 to February 2021. The instrument is in the form of a questionnaire in descriptive statistical analysis. The results of the research data concluded that the level of customer satisfaction in the very satisfied category was 91% and 7% satisfied.